Differential synapse formation and neurite outgrowth at two branches of the metacerebral cell of Aplysia in dissociated cell culture - Schacher, S (J Neurosci, 1985)
The metacerebral cell (MCC) of Aplysia californica was isolated with its bifurcate axon from the cerebral ganglion and maintained in vitro under three conditions: (a) with no targets, (b) with identified buccal ganglion neurons B1 or B2 placed near the stump of the large diameter cerebral-buccal connective (CBC) branch, and (c) with B1 or B2 placed near the stump of the small diameter posterior lip nerve (PLN) branch. After 5 days in culture, the two branches differed significantly in the formation of chemical connections and in the extent of neurite outgrowth. Chemical connections characteristic of MCC-B1(B2) connections in vivo were observed in more than 90% of the cultures in which the buccal neuron was contacted by neurites emerging from the CBC branch, but in only 20% of the cultures in which the buccal neuron was contacted by neurites extending from the PLN branch. Neurite outgrowth from the CBC stump was always greater than growth from the PLN and was not affected significantly by the presence of a buccal neuron target at either branch. In contrast, neurite outgrowth from the PLN decreased significantly when the target was contacted by neurites from the CBC branch. These results suggest that two branches of a single neuron can differ in their capacities to form chemical connections. In addition, the two branches show differential growth as a result of target interaction at one of the branches. This simple in vitro system may therefore be useful in exploring the ways in which individual neurons control neurite extension from different branches as they seek to form chemical connections with their targets.